Parents’ Perception: Roles and Involvement in Distance Learning Amid the Covid-19 Pandemic - Yohana Eva Mau Kasi; Suparno Suparno; Abdul Asib (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study was to ascertain parents' perceptions of their roles in mapping students' English learning achievement and identifying their involvements and strategies for involvement in students' English learning achievement amid the Covid-19 pandemic at a private junior high school in Kupang, East Nusa Tenggara province, Indonesia. The study is qualitative in nature and employs a case study design. The questionnaire and interview were made public in this study. Additionally, a descriptive model was utilized to examine the data. The findings suggested that parents agreed on their roles and responsibilities in mapping their children's English learning achievement. Certain parents considered their duties and involvement were critical, even more so during the Covid-19 epidemic, during which children spent most of their time at home. Parents believed that supporting, motivating, and directing their children's roles might aid the school and their children's English learning. Additionally, English teachers are expected to act like parents, monitoring, guiding, and acknowledging their students' assignments. Additionally, parents actively participated in school activities like teacher-parent online sessions to interact and discuss their children's academic success during the Covid-19 pandemic.